2001
DOI: 10.1248/bpb.24.841
|View full text |Cite
|
Sign up to set email alerts
|

Rikkunshi-to Raises Levels of Somatostatin and Gastrin in Human Plasma.

Abstract: Rikkunshi-to, a traditional Chinese (Kampo) herbal medicine, is prepared from eight crude herbs: Ginseng Radix, Atractylodis Rhizoma, Hoelen, Pinelliae Tuber, Aurantii Nobilis Pericarpium, Zizyphi Fructus, Glycyrrhizae Radix, and Zingiberis Rhizoma. This medicine was evaluated for its clinical usefulness in the treatment of chronic hypofunctions of gastrointestinal tract including gastric flatulence, anorexia, nausea, and vomiting. Recently, those effects of Rikkunshi-to were proved to be based on increased bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 28 publications
0
25
0
1
Order By: Relevance
“…Previously, the acceleration of gastric emptying (1, 10), the increase in plasma somatostatin and gastrin levels (11), and the stimulation of gastric myoelectric activity after gastrointestinal surgery (12) were reported as clinical effects of Rikkunshi-to. On the other hand, some basic studies have demonstrated that Rikkunshi-to prevents gastric mucosal damage (13,14) and recovers the gastric adaptive relaxation (GAR) abolished by treatment with L-NNA in the isolated guinea pig stomach (15).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the acceleration of gastric emptying (1, 10), the increase in plasma somatostatin and gastrin levels (11), and the stimulation of gastric myoelectric activity after gastrointestinal surgery (12) were reported as clinical effects of Rikkunshi-to. On the other hand, some basic studies have demonstrated that Rikkunshi-to prevents gastric mucosal damage (13,14) and recovers the gastric adaptive relaxation (GAR) abolished by treatment with L-NNA in the isolated guinea pig stomach (15).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the empirical results, the effects are assumed to be due to changes in the levels of gut-motor regulatory hormones (i.e., SS, gastrin, motilin, and VIP). 39,40) On the other hand, these Kampo medicines regulate plasma ACTH and cortisol levels in the HPA axis. 23) In addition to these actions, Rikkunshi-to and Hange-shashin-to were found to affect plasma NPY levels in this study.…”
Section: Fig 2 Elution Profiles Of Plasma Extracts By Hplc On a C 1mentioning
confidence: 99%
“…Naito et al investigated several Kampo medicines, including Pinelliae Tuber and Zingiberis Rhizoma. [4][5][6] Kampo medicines, such as Rikkunshi-to, Hange-shashin-to and Hange-koboku-to, usually use longterm administration to treat chronic hypofunction. But the Kampo medicines that consist of multiple herbs, such as Sho-hange-ka-bukuryo-to, are administered to treat acute hypofunction.…”
Section: -3)mentioning
confidence: 99%
“…10) On Kampo medicine, Nagano et al investigated the effect of Daikenchu-to on gastrointestinal peptides, 1,2) and Naito et al also reported the effects of some Kampo medicines on gastrointestinal peptides. [4][5][6]11) On the gastroprotective function as a neural emergency system, sensory afferent neurons in the gastrointestinal mucosa regulate neuropeptide (calcitonin gene-related peptide (CGRP), and tachykinins (substance P etc.)) levels and play various physiological roles.…”
mentioning
confidence: 99%